53 A retrospective chart review of all patients with an out-of-hospital cardiac arrest (ooh ca) presenting to the royal berkshire hospital (rbh) nhs foundation trust 2018 - 2021: post-resuscitation care based on the cardiovascular disease outcomes strategy drives improved patient survival. (6th June 2022) - Keating, Liza; Orr, Will; Johnson, Shona; Realey, Tracey; Vettikumaran, Shamba; Maton, Suzy
Abstract : Background: In England, overall around 9% of patients who undergo an OOHCA survive to hospital discharge. Post-resuscitation care remains the least well-defined component of the crucial 'chain of survival', and was a focus of the 2013 Cardiovascular Disease Outcomes Strategy. At the RBH we have collaborated across teams with the emergency medical services (EMS), emergency department (ED), cardiology and critical care working to improve outcomes and ensure the right patients undergo timely angiography and percutaneous intervention (PCI) with subsequent admission to critical care, see figure one.In 2016, we analysed 3428 patients with OOHCA presenting to the RBH between October 2012 and May 2015 and established a local OOHCA protocol in collaboration with EMS, ED, interventional cardiology and critical care and demonstrated better than expected survival to hospital discharge at 19.5%. Aim: The aim of this review was to ascertain if the currently observed outcomes, which were previously better than expected at 19.5%, have been maintained. Methods: We undertook a retrospective chart review of EMS data, ED records, Myocardial ischaemia National Audit Project (MINAP) and Trust coding data from 2018 to 2021. We identified 5785 adult patients with spontaneous OOHCA in which cardiopulmonary resuscitation was commenced or continued by EMS. Outcomes for the RBH were compared to current national statistics and to our previous 2012- 2015 data. A chi-squared test to evaluate comparison of proportions was used. Results: Overall locally 21.7% of patients with an OOHCA survived to discharge compared to 9.1% for England (P<0.0001), see table one. A greater proportion than in the previous audit (32.6% vs 22%) underwent coronary intervention. Although survival to hospital discharge in those undergoing PCI was lower in 2018 – 2021 at 51.5% compared to 62.4% in 2012 – 2015, see table two. Further work is ongoing to quantify the degree of disability exists in survivors in the more recent audit using the Glasgow Outcome Score. Conclusion: Through collaborative working across the patient pathway high survival rates at the RBH have been maintained for all patients admitted to critical care following an OOH CA compared to the national average. Conflict of Interest: nil